2011
DOI: 10.1007/s11426-010-4195-5
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and potential application of functional ordered microstructures

Abstract: With the development of science and technology, ordered microstructures with special functions have aroused intense research interest. These functional microstructures have been widely used in fields of microelectronic devices, micro-reactors, biochemical sensors and optical devices, etc. This paper summaries our work on preparation and application of microscopic patterned surfaces with ordered microstructures, and looks into the future development of this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…108 The d s-s can be well regulated by controlling the dip-coating speed and the concentration of colloidal particles. In addition to the preparation of 2D NPCs by RIE and self-assembly, a soft lithography technique for the preparation of 2D NPCs was reported by Yang et al [114][115][116][117] As shown in Fig. 3a, a layer of close-packed 2D PCs was transferred to the surface of PDMS stamps, and the solvent was used to swell the PDMS to increase the lattice distance to obtain nonclosely packed structures.…”
Section: D Npcsmentioning
confidence: 99%
“…108 The d s-s can be well regulated by controlling the dip-coating speed and the concentration of colloidal particles. In addition to the preparation of 2D NPCs by RIE and self-assembly, a soft lithography technique for the preparation of 2D NPCs was reported by Yang et al [114][115][116][117] As shown in Fig. 3a, a layer of close-packed 2D PCs was transferred to the surface of PDMS stamps, and the solvent was used to swell the PDMS to increase the lattice distance to obtain nonclosely packed structures.…”
Section: D Npcsmentioning
confidence: 99%